2021
DOI: 10.1093/arclin/acab012
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Its Implications for Neuropsychological Evaluation

Abstract: Objective In the background of a large population of bilinguals globally, the study aimed to develop standards of neuropsychological testing in the context of bilingualism. Because bilingualism is known to affect cognitive processes, bilinguals and monolinguals were compared on their performance on cognitive tests, to investigate the possibility of the need for separate normative data for the two groups. Method A comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In 23 studies (Ansaldo et al., 2015; Bialystok et al., 2008; Blumenfeld et al., 2016; Bogulski et al., 2015; Cáceres‐Luna et al., 2021; Friesen et al., 2015; Kousaie et al., 2014; Kowoll et al., 2015; Ljungberg et al., 2013, 2020; Luo et al., 2010; Massa et al., 2020; Paplikar et al., 2021; Patra et al., 2020; Prior & Gollan, 2011; Sadat et al., 2016; Soltani et al., 2021; Taler et al., 2013; Torres et al., 2022; Vega‐Mendoza et al., 2015; Woumans et al., 2015, 2019; Zeng et al., 2019) no significant difference emerged between monolingual and bilingual participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 23 studies (Ansaldo et al., 2015; Bialystok et al., 2008; Blumenfeld et al., 2016; Bogulski et al., 2015; Cáceres‐Luna et al., 2021; Friesen et al., 2015; Kousaie et al., 2014; Kowoll et al., 2015; Ljungberg et al., 2013, 2020; Luo et al., 2010; Massa et al., 2020; Paplikar et al., 2021; Patra et al., 2020; Prior & Gollan, 2011; Sadat et al., 2016; Soltani et al., 2021; Taler et al., 2013; Torres et al., 2022; Vega‐Mendoza et al., 2015; Woumans et al., 2015, 2019; Zeng et al., 2019) no significant difference emerged between monolingual and bilingual participants.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Paplikar et al. (2021) suggested that assessments of bilinguals should be conducted in their dominant language and that responses in their second known language should also be considered in the scoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borrowed words (words incorporated from one language into another by a community of speakers) and language mixed words (words from the nontarget languages) were considered as a response in native and other language, respectively. The total score was calculated by adding the correct responses in native and other languages (Paplikar, Alladi et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Language of assessment was determined using the Language Use Questionnaire (LUQ; Vasanta et al., 2010) to measure the language choice, proficiency and pattern of language use in different contexts. Participants having > 70% proficiency and language choice scores in any of these languages (Hindi, Bengali, Telugu, Kannada and Malayalam) on LUQ were tested in the respective language (Paplikar, Vandana et al., 2021). Average time taken to complete the PNT was 7–10 min in healthy controls and 15–20 min in patients with dementia and MCI depending on the severity of the disease.…”
Section: Methodsmentioning
confidence: 99%